The relationship between self-efficacy and aggressive behavior in boxers: The mediating role of self-control - Chen, X.; Zhang, G.; Yin, X.; Li, Y.; Cao, G.; Gutiérrez-Garcia, C.; Guo, L. (Frontiers in Physiology, 2019)
Aggressive behavior has been one of the core issues in sports psychology, whereas boxers` aggressive behavior has received limited attention. Although some literature reported that self-efficacy is related to aggressive behavior, the mechanism whereby self-efficacy affects aggressive behavior remains unclear. The present study investigated the relationship between self-efficacy and aggressive behavior, as well as the effect of self-control as a mediating factor. This study uses the Self-efficacy Scale for Athletes, the Self-control Questionnaire for Athletes, and the Buss-Perry Aggression Questionnaire. This relationship is explored through self-reported measures from N = 414 Chinese professional boxers, n = 243 were male and n = 171 were female, the average age was M = 17.72 years (SD = 3.147), the participants, the average number of years of exercise was M = 3.89 years (SD = 2.734); Results showed that male boxers reported greater aggression than female boxers; It was found that the self-efficacy and self-control improved as age of the participants increased; The higher the level of competition, the higher levels of self-efficacy and self-control; Self-efficacy was negatively related with aggressive behavior and positively correlated with self-control. Self-control was also negatively correlated with aggressive behavior among boxers. Self-control had a full mediating effect on the relationship between self-efficacy and aggressive behavior.